2016
DOI: 10.1016/j.bbmt.2015.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Hypomethylating Agents before Allogeneic Stem Cell Transplant Improves Progression-Free Survival for Patients with Chronic Myelomonocytic Leukemia

Abstract: The treatment of patients with chronic myelomonocytic leukemia (CMML) with transplant has not been optimized. We retrospectively reviewed the data for 83 consecutive patients with CMML (47 with CMML-1/2 and 36 with CMML progressed to acute myeloid leukemia) who received an allogeneic stem cell transplant at our institution between April 1991 and December 2013 to identify factors associated with improved survival and determine whether treatment with hypomethylating agents before transplant improves progression-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 37 publications
4
49
0
Order By: Relevance
“…The median age of our patients was 57 years, older than in other reported studies. 1118, 22 The median follow up in our study is 51 months, longer than in most other reported studies. 1113, 1518, 2327 Subjects underwent either myeloablative or RIC preparative regimen.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The median age of our patients was 57 years, older than in other reported studies. 1118, 22 The median follow up in our study is 51 months, longer than in most other reported studies. 1113, 1518, 2327 Subjects underwent either myeloablative or RIC preparative regimen.…”
Section: Discussionmentioning
confidence: 50%
“…This is contrary to a recent publication from Kongtim et al that reports lower relapse and improved progression-free survival for patients treated with hypomethylating agents prior to alloHCT. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for Allo-HSCT results in CMML can be found in the reports on allo-HSCT in MDS and MPN or in retrospective studies on small number of CMML transplanted patients. There are no randomized prospective (Table 2) [20][21][22][23][24][25][26][27][28][29][30][31]. In 2015 two reports ''specifically'' focused on the evolution of allo-HCST in CMML appeared.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multicenter retrospective study with 1,656 CMML patients of whom 89 received an allogeneic HCT demonstrated the benefit of HCT for patients with higher-risk disease as determined by the CPSS 11 and multiple retrospective studies have documented a 3-year OS rate of 30-40%. [12][13][14][15] For high-risk transplant-ineligible and/or lower-risk patients the most widely used therapies are hydroxyurea, hypomethylating agents, and best supportive care. Recent evidence suggests that hypomethylating agents might be superior to hydroxyurea.…”
mentioning
confidence: 99%